Molecular Characterization of the Glycerol-Oxidative Pathway of Clostridium butyricum VPI 1718 - Raynaud, Céline (American Society for Microbiology, 2011)
The glycerol oxidative pathway of Clostridium butyricum VPI 1718 plays an important role in glycerol dissimilation. We isolated, sequenced, and characterized the region coding for the glycerol oxidation pathway. Five open reading frames (ORFs) were identified: dhaR, encoding a putative transcriptional regulator; dhaD (1,142 bp), encoding a glycerol dehydrogenase; and dhaK (995 bp), dhaL (629 bp), and dhaM (386 bp), encoding a phosphoenolpyruvate (PEP)-dependent dihydroxyacetone (DHA) kinase enzyme complex. Northern blot analysis demonstrated that the last four genes are transcribed as a 3.2-kb polycistronic operon only in glycerol-metabolizing cultures, indicating that the expression of this operon is regulated at the transcriptional level. The transcriptional start site of the operon was determined by primer extension, and the promoter region was deduced. The glycerol dehydrogenase activity of DhaD and the PEP-dependent DHA kinase activity of DhaKLM were demonstrated by heterologous expression in different Escherichia coli mutants. Based on our complementation experiments, we proposed that the HPr phosphoryl carrier protein and His9 residue of the DhaM subunit are involved in the phosphoryl transfer to dihydroxyacetone-phosphate. DhaR, a potential regulator of this operon, was found to contain conserved transmitter and receiver domains that are characteristic of two-component systems present in the AraC family. To the best of our knowledge, this is the first molecular characterization of a glycerol oxidation pathway in a Gram-positive bacterium.